Prediction of water-adulteration within honey by air-line de-embedding waveguide measurements. (July 2021) - Hasar, Hafize; Hasar, Ugur Cem; Kaya, Yunus; Ozturk, Hamdullah; Izginli, Mucahit; Ozbek, Ibrahim Yucel; Oztas, Taskin; Canbolat, Mustafa Yildirim; Ertugrul, Mehmet
Abstract: An efficient de-embedding air-line microwave method has been proposed for accurate relative complex permittivity, ε r = ε r ′ − i ε r ′ ′, measurement of water-adulteration level within honey. It could be effectively applied to eliminate the errors arising from usage of imperfect calibration standards because it bypasses the requirement of these standards. Its accuracy is improved by utilizing the unitary and similarity properties of a passive two-port network, and then is compared with the accuracy of a calibration-dependent method present in the literature by using normalized root-mean-square-error (N-RMSE) values of ε r ′ and ε r ′ ′ of distilled water, in reference to the Debye value. From this comparison, it is observed that N-RMSE values calculated for ε r ′ (and ε r ′ ′ ) by using this calibration-dependent method and the (improved) proposed method are, respectively, around 0.1955 (0.1002) and 0.1962 (1.1067), indicating a good agreement between them. After validation the proposed de-embedding method using distilled water measurements, tested pure honey was adulterated with distilled water by different percentage values δ ranging from 1% to 10% in 1% increments. It is observed that the maximum distance between extracted ε r ′ (or ε r ′ ′ ) values of adulterated honey by the applied calibration-dependent method and the proposed method is less than 2%. Afterward, an empirical formula was devised to fit ε r ′ and ε r ′ ′ values from measured ε r of water-adulterated honey with various δ levels. It is noted that extracted ε r ′ is much more better fitted than extracted ε r ′ ′, especially for δ ≤ 4 . Next, an optimization process is followed to evaluate the frequency for optimum prediction of adulteration levels using the empirical formula based on ε r ′ or ε r ′ ′ . It is noticed that optimized δ values using the empirical formula based on ε r ′ (with an average prediction error of around 0.071 at 4.5 GHz) are superior to optimized δ values using the empirical formula based on ε r ′ ′ (with an average prediction error of around 0.085 at 4.2 GHz) for prediction of previously known δ values. Sensitivity and uncertainty analyses were performed to assess and improve the accuracy of the proposed method. Graphical abstract: Highlights: Calibration-free de-embedding method for detection of water adulteration in honey. Establishing a close link between permittivity of honey and water-adulteration level. Obtaining an empirical formula for prediction of water-adulteration level. Measurement frequency is optimized for optimum prediction of adulteration levels. Adulteration-levels of 1–10% (with 1% increment) are accurately predicted.